PROSPECTS FOR EFFECTIVE USE OF BUDGETARY FUNDS IN PUBLIC FINANCE MANAGEMENT - Razzaqov Jasur Xamrabayevich (Scholars Digest Publishing, 2023)
The article analyzes the theoretical and methodological substantiation of program budgeting and the development of practical recommendations for the formation and development of program budgeting at the local level.
Keywords: analysis, budgeting, budget, public finance, funds.